2008
DOI: 10.1182/blood-2007-10-116285
|View full text |Cite
|
Sign up to set email alerts
|

The tetraspanin CD63 is involved in granule targeting of neutrophil elastase

Abstract: Targeting mechanisms of neutrophil elastase (NE) and other luminal proteins stored in myeloperoxidase (MPO)-positive secretory lysosomes/primary granules of neutrophils are unknown. These granules contain an integral membrane protein, CD63, with an adaptor protein-3-dependent granule delivery system. Therefore, we hypothesized that CD63 cooperates in granule delivery of the precursor of NE (proNE). Supporting this hypothesis, an association was demonstrated between CD63 and proNE upon coexpression in COS cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 42 publications
1
27
0
Order By: Relevance
“…Our and other published data (Kallquist et al, 2008; Michaux and Cutler, 2004) show that CD63 in specialized cells is predominantly associated with LROs and their endosomal precursors, suggesting a specific role in LRO formation and/or function as proposed (Pols and Klumperman, 2009). Consistently, whereas lysosomal defects are not detected in CD63 knockout mice (Schroder et al, 2009), these mice do harbor altered LROs, as shown here for melanosomes.…”
Section: Discussionsupporting
confidence: 80%
“…Our and other published data (Kallquist et al, 2008; Michaux and Cutler, 2004) show that CD63 in specialized cells is predominantly associated with LROs and their endosomal precursors, suggesting a specific role in LRO formation and/or function as proposed (Pols and Klumperman, 2009). Consistently, whereas lysosomal defects are not detected in CD63 knockout mice (Schroder et al, 2009), these mice do harbor altered LROs, as shown here for melanosomes.…”
Section: Discussionsupporting
confidence: 80%
“…CD63, an abundant membrane protein of primary granules, is sorted by AP-3, and has been shown to play a role in granule protein quality control since it can be trafficked from many membranes to granules (40, 41). A recent study showed that CD63 and neutrophil elastase are present in a complex, highly indicative of a role for CD63 in the targeting of elastase to primary granules (42). Other serine proteases affected by CD63 granule sorting include proteinase-3 (39), and possibly the cathepsin family of proteases, which exhibit varying degrees of M6P-dependent/independent sorting (36, 4345).…”
Section: Neutrophil Granularitymentioning
confidence: 99%
“…It is, therefore, likely that TIMP-1 directly acts on hematopoietic progenitors, triggering their differentiation towards the granulocytic lineage. As CD63 itself is described to regulate activation and adhesion of mature neutrophils to endothelium, 51 granule targeting and release, 52 and is up-regulated on apoptotic neutrophils, 53 TIMP-1 /CD63 interactions may have additional effects on mature neutrophils.Our observations were made on mice, where neutrophil blood counts are generally lower than in humans. 34 Therefore, it remains to be shown whether high TIMP-1 levels have a similar effect on the human hematopoietic system.…”
mentioning
confidence: 99%
“…It is, therefore, likely that TIMP-1 directly acts on hematopoietic progenitors, triggering their differentiation towards the granulocytic lineage. As CD63 itself is described to regulate activation and adhesion of mature neutrophils to endothelium, 51 granule targeting and release, 52 and is up-regulated on apoptotic neutrophils, 53 TIMP-1 /CD63 interactions may have additional effects on mature neutrophils.…”
mentioning
confidence: 99%